2006
DOI: 10.1128/aem.72.5.3524-3530.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Single Monooxygenase, Ese, Is Involved in the Metabolism of the Organochlorides Endosulfan and Endosulfate in an Arthrobacter sp

Abstract: In this paper we describe isolation of a bacterium capable of degrading both isomers of the organochloride insecticide endosulfan and its toxic metabolite, endosulfate. The bacterium was isolated from a soil microbial population that was enriched with continuous pressure to use endosulfate as the sole source of sulfur. Analysis of the 16S rRNA sequence of the bacterium indicated that it was an Arthrobacter species. The organochloridedegrading activity was not observed in the presence of sodium sulfite as an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 31 publications
5
59
0
2
Order By: Relevance
“…Redox reactions are known in bacteria that can degrade and detoxify endosulfan but to the best of our knowledge, no hydrolytic mechanism for degrading this insecticide has been characterised in any organism to date. 75,76) Nor is it obvious at this point how endosulfan could bind to and be sequestered by an overexpressed esterase, although we have found at least one other report of competitive inhibition of heliothine esterases by another organochlorine (in that case, DDT). 22) Interestingly, there is evidence that esterase-mediated SP resistance in H. armigera leads to negative cross-resistance to the oxadiazine indoxacarb.…”
Section: Heliothine Resistance To Other Insecticidesmentioning
confidence: 84%
“…Redox reactions are known in bacteria that can degrade and detoxify endosulfan but to the best of our knowledge, no hydrolytic mechanism for degrading this insecticide has been characterised in any organism to date. 75,76) Nor is it obvious at this point how endosulfan could bind to and be sequestered by an overexpressed esterase, although we have found at least one other report of competitive inhibition of heliothine esterases by another organochlorine (in that case, DDT). 22) Interestingly, there is evidence that esterase-mediated SP resistance in H. armigera leads to negative cross-resistance to the oxadiazine indoxacarb.…”
Section: Heliothine Resistance To Other Insecticidesmentioning
confidence: 84%
“…Esd did not degrade either α-endosulfan or the metabolites of endosulfan and endosulfan sulphate. Wier et al [24] have reported the gene Ese encoding enzyme from monooxygenase family capable of degrading both endosulfan α and β from Arthrobacter sp. After, understanding the gene of interest and enzyme involved, the Superbugs can be created to achieve the desired result at fast rate in short time frame.…”
Section: Recent Developments In Pesticide Biodegradationmentioning
confidence: 99%
“…The sulphur-containing intermediate of endosulfate metabolism has been identifi ed as endosulfan hemisulfate (Fig. 2) [14]. The equivalent metabolite for endosulfan metabolism, endosulfan hemisulfi te, was not detected and likely undergoes rapid desulfurisation to form endosulfan monoalcohol.…”
Section: Oxidoreductases: Gox (Ec 158)mentioning
confidence: 99%